Propagação Vegetativa de Sobreiros Seleccionados - de Freitas, Maria Isabel Carrasquinho (Silva Lusitana, 2002)
The aim of this investigation was to evaluate the possibilities of vegetative propagation techniques of adult cork oak trees so as to develop an approach applicable to a genetic improvement breeding program. Bud grafting and cuttings were used to multiply and mass propagate selected cork oak trees. Forty-six cork oak trees were reproduced from clone banks. September proved to be a better season for grafting than June/July. Rooting season and the temperature of the rooting substrate were demonstrated to be important factors in juvenile cuttings response. The highest rooting ability was achieved in August with a rooting substrate temperature of 28°C (57.0%). The best rooting rate was obtained by maintaining cuttings in rooting media for four months. The application of IBA influenced rooting ability both in cuttings from seedlings and those from the clone bank. Nevertheless, juvenile material needed a lower IBA concentration (0.5%) than the older material (1%). The clone and age of grafting were shown to influence the rooting ability. The decrease of rooting ability with age of grafting requires a dynamic management of the clone bank. The vegetative propagation of selected adult cork oak trees seems to be a viable technique, establishing a prior clone bank, by means of grafting, and then mass propagation through cuttings of this material.
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: Bud grafting; Clones; Cuttings; Quercus suber L.; vegetative propagation